2008
DOI: 10.1007/s10562-008-9595-1
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of the Henry Reaction Products: Nitroalcohol Versus Nitrostyrene by a Simple Change of Amino-Groups of Aminofunctionalized Nanoporous Catalysts

Abstract: A synthetic method for controlling the Henry reaction products from nitrostyrene to nitroalcohol in heterogeneous catalysis by a simple change of the catalytic sites in organoamine-functionalized mesoporous catalysts is reported. The synthesis resulted in either b-nitrostyrene or b-nitroalcohol by simple change of the types of amine functional groups in the amine-functionalized mesoporous catalysts from primary amines into secondary or tertiary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…[25,26] Solin and collaborators, as well as Thiel and co-workers, obtained similar results, using different combinations of alkylamines and acidic groups in mesoporous silica supports. [23,27] However, the poor catalytic activity of monofunctional amine on silica, which remains commonly used for the aldol and similar types of condensation, [20,22,24,[29][30][31][32] is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] Solin and collaborators, as well as Thiel and co-workers, obtained similar results, using different combinations of alkylamines and acidic groups in mesoporous silica supports. [23,27] However, the poor catalytic activity of monofunctional amine on silica, which remains commonly used for the aldol and similar types of condensation, [20,22,24,[29][30][31][32] is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The Knoevenagel reaction has been conducted with aminopropylfunctionalized MCM-41-type mesoporous silica, [95] and interestingly, the understanding gained within this reaction marked the starting point to elucidate the role of the outer-sphere polarity surrounding a tethered catalyst on the chemical reactivity of the heterogeneous catalyst. [96,97] In this framework, Reddy et al reported the use of chitosan hydrogel microspheres for the Knoevenagel reaction of a set of aromatic aldehydes (para-nitrobenzaldehyde, para-chlorobenzaldehyde, naphthaldehyde, para-tolualdehyde, and paramethoxybenzaldehyde) by using three different activated methylenes (malonitrile, ethylcyanoacetate, and diethylmalonate; Scheme 5). [98] With DMSO as a solvent, and at room temperature, the reactants readily condense to provide the expected dehydrated products in good yields and selectivity.…”
Section: Knoevenagel Reactionmentioning
confidence: 99%
“…In particular, mesoporous silica-supported amines have been widely shown to serve as heterogeneous catalysts for the Henry reactions between various substituted benzaldehydes and nitroalkanes. [50][51][52][53][54][55] The products of these reactions were reported to be predominantly the dehydrated C-C coupling products such as substituted nitrostyrenes. In some instances or under some reaction conditions, however, the Henry reaction could generate the nondehydrated products or even the Michael addition products.…”
Section: Henry Reactionmentioning
confidence: 99%